Exploring the variables influencing the immune response of traditional and innovative glycoconjugate vaccines - Micoli, Francesca; Stefanetti, Giuseppe; MacLennan, Calman A. (Frontiers in Molecular Biosciences, 2023)
Vaccines are cost-effective tools for reducing morbidity and mortality caused by infectious diseases. The rapid evolution of pneumococcal conjugate vaccines, the introduction of tetravalent meningococcal conjugate vaccines, mass vaccination campaigns in Africa with a meningococcal A conjugate vaccine, and the recent licensure and introduction of glycoconjugates against S. Typhi underlie the continued importance of research on glycoconjugate vaccines. More innovative ways to produce carbohydrate-based vaccines have been developed over the years, including bioconjugation, Outer Membrane Vesicles (OMV) and the Multiple antigen-presenting system (MAPS). Several variables in the design of these vaccines can affect the induced immune responses. We review immunogenicity studies comparing conjugate vaccines that differ in design variables, such as saccharide chain length and conjugation chemistry, as well as carrier protein and saccharide to protein ratio. We evaluate how a better understanding of the effects of these different parameters is key to designing improved glycoconjugate vaccines.